2012
DOI: 10.1186/1477-7525-10-120
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Clot Treatment Scale (ACTS) in clinical trials: cross-cultural validation in venous thromboembolism patients

Abstract: BackgroundThe Anti-Clot Treatment Scale (ACTS) is a 15-item patient-reported instrument of satisfaction with anticoagulant treatment. It includes a 12-item ACTS Burdens scale and a 3-item ACTS Benefits scale. Its role in clinical trials and other settings should be supported by evidence that it is both clinically meaningful and scientifically sound. The aim of the study was to evaluate the measurement performance of the ACTS (Dutch, Italian, French, German and English language versions) in patients with venous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
105
5
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(123 citation statements)
references
References 39 publications
7
105
5
2
Order By: Relevance
“…The ACTS fulfills these requirements and aims to delineate the burdens and benefits associated with anticoagulation treatment [9]. Both the ACTS Burdens and ACTS Benefits scales consistently satisfied traditional reliability and validity criteria across multiple language populations (including French language), supporting the fact that it is a clinically useful patient-reported instrument of satisfaction with anticoagulant treatment in clinical trials [10]. The SAFARI study has provided robust data on the patient-reported burden and benefit of the switch from VKA to rivaroxaban in this patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACTS fulfills these requirements and aims to delineate the burdens and benefits associated with anticoagulation treatment [9]. Both the ACTS Burdens and ACTS Benefits scales consistently satisfied traditional reliability and validity criteria across multiple language populations (including French language), supporting the fact that it is a clinically useful patient-reported instrument of satisfaction with anticoagulant treatment in clinical trials [10]. The SAFARI study has provided robust data on the patient-reported burden and benefit of the switch from VKA to rivaroxaban in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…The ACTS was scored in accordance with the developers’ guidelines [10]. The score for each item was obtained by means of a 5-response Likert rating scale (1 –Not at all, 2 –A little, 3 –More or less, 4 –A lot, 5 –Extremely).…”
Section: Methodsmentioning
confidence: 99%
“…Illness beliefs, medication beliefs, and treatment satisfaction/anticoagulation‐specific quality of life were assessed using a questionnaire pack comprised of the Revised Illness Perceptions Questionnaire (IPQ‐R), the Beliefs about Medicines Questionnaire (BMQ), and the Anti‐Clot Treatment Scale (ACTS), respectively 31, 32, 33. Questions in the IPQ‐R and BMQ are answered on a 5‐point Likert scale “strongly disagree” ascending to “strongly agree” which are scored as 1 and 5, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Specific necessity determines the extent the patient recognises the need for VKA therapy, while the specific concern subscale determines how strong their anxieties towards VKAs are 32. The ACTS measures anticoagulation‐specific QoL and treatment satisfaction on two subscales: benefits and burdens of anticoagulation therapy 33, 34. For descriptions of all subscales see Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The ACTS is a 17-item, patient-reported measure of satisfaction with anticoagulant treatment. 9 It includes 13 items concerning the burdens of anticoagulant treatment (items 1-12 plus 1 global question about burdens) and 4 items concerning the benefits of anticoagulant treatment (items 14-16 plus 1 global question about benefits). Each of the items is scored on a 5-point Likert scale (1 = not at all; 2 = a little; 3 = moderately; 4 = quite a bit; 5 = extremely).…”
mentioning
confidence: 99%